Penerapan Model Pembelajaran ATI (Aptitude Treatment Interaction) untuk Meningkatkan Keaktifan Belajar IPA - Suastini, Ni Putu (Journal of Education Action Research, 2018)
The purpose of this study was to determine the improvement of science learning participation of fourth grade students of SD N 3 Sibang Kaja in the first semester of the academic year 2016/2017 after the implementation of the ATI learning model (Aptitude Treatment Interaction). The type of this research was classroom action research (CAR). The research subjects were 20 students of the fourth grade students. The learning participation data was collected by observation sheet. The data obtained were analyzed using descriptive statistical analysis. Based on the results of the research that has been done, it can be concluded that the application of the Aptitude Treatment Interaction (ATI) learning model can increase the students’ learning participation in science. This can be seen from the improvement of the average score. In the first cycle the average score of the students was 15.35 and it was become 21.30 in the second cycle. The classical completeness of students also increased from 55% in the first cycle to 95% in the second cycle.